The Effect of Relational and Interactive Aspects of Parasocial Experiences on Attitudes and Message Resistance. (1st September 2016) - Tukachinsky, Riva; Sangalang, Angeline
Abstract : This study examines direct and interaction effects of parasocial interactions (PSIs) and relationships (PSRs) on message resistance (reactance and counterarguing) and message-consistent attitudes. PSI involves the give-and-take within the media encounter, whereas PSR entails the relational bonding with the media figure that continues to exist outside the context of any particular media exposure. A 2 (high/low PSI) × 2 (high/low PSR) experiment revealed that PSI (but not PSR) can increase message resistance, particularly when PSR is low. No significant effects of PSR/PSI on attitudes were found. The study suggests that, contrary to past theorization, PSIs may facilitate, rather than reduce, message resistance. Furthermore, the findings highlight the importance of considering PSIs and PSRs as distinct constructs in media effects research.